1995
DOI: 10.1136/fn.73.1.f32
|View full text |Cite
|
Sign up to set email alerts
|

Use of the CRIB (clinical risk index for babies) score in prediction of neonatal mortality and morbidity.

Abstract: A prospective study ofthe outcome of care of a regional cohort of very low birthweight (<1500 g) and very preterm (<32 weeks) infants was carried out. Its aims were to assess the ability of the CRIB (clinical risk index for babies) score, rather than gestational age or birthweight, to predict mortality before hospital discharge, neurological morbidity, and length of stay, and to access CRIB score as an indicator of neonatal intensive care performance. 676 live births fulfilled the criteria and complete data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 17 publications
1
48
0
Order By: Relevance
“…[4][5][6]8,10,13 Analysis of the predictive accuracy of birthweight, gestational age and CRIB score in relation to the risk of mortality, undergone by building a ROC curve, within the current study, determined that the CRIB scores greater than 4 present the best characteristics as a diagnostic test when compared to birthweight <1,005 g and gestational age <28 weeks. As in previous studies, the present investigation has demonstrated that the CRIB score is more accurate, with an area under the ROC curve of 0.88 (CI 95%: 0.84-0.92), differing significantly from birthweight, which has an area of 0.76 (CI 95%: 0.71-0.81).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[4][5][6]8,10,13 Analysis of the predictive accuracy of birthweight, gestational age and CRIB score in relation to the risk of mortality, undergone by building a ROC curve, within the current study, determined that the CRIB scores greater than 4 present the best characteristics as a diagnostic test when compared to birthweight <1,005 g and gestational age <28 weeks. As in previous studies, the present investigation has demonstrated that the CRIB score is more accurate, with an area under the ROC curve of 0.88 (CI 95%: 0.84-0.92), differing significantly from birthweight, which has an area of 0.76 (CI 95%: 0.71-0.81).…”
Section: Discussionmentioning
confidence: 92%
“…11,12,16 Data from studies undertaken by the International Neonatal Network, in tertiary hospitals in the United Kingdom among newborns weighing less than 1500 g and/or less than 31 weeks gestational age, were analyzed and predictors for mortality were developed and proposed in 1993. 16 Since then, the CRIB score has been utilized in different neonatal units, 3,4,6,8,13 because it is a simple instrument which is sensitive and can be rapidly applied. It stresses parameters which reflect the physiological conditions of the newborn soon after birth and supercedes the disadvantages of birthweight specific and/or gestational age specific predictors of neonatal mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The NICHD score was developed in the United States (n ÂŒ 3603 infants 501 to 1500 g) 17 although with occasional poor performance and no better than birth weight alone. 18,19 In recent years, Pollack et al 20 has published risk models in a cohort of VLBW infants from the Washington, DC area. They found that these scores overpredicted mortality indicating a need for frequent recalibration.…”
Section: Discussionmentioning
confidence: 99%
“…The Clinical Risk Index for Babies (CRIB) [9] is one of the most widely used scores [8,10], validated in a variety of studies [11,12,13,14,15,16,17]. However, it has been criticized for its inclusion of the applied fraction of inspired oxygen (FiO 2 ), which is adjusted by the physician.…”
Section: Introductionmentioning
confidence: 99%